Analysis of The Quality of Biology Learning Media In The Form Of Macroarthropodarium Complete With Leaflets - Hasana, Fitratul; Amalia, Hilda Ayu Melvi; Rosmini, Rosmini (Biopedagogia, 2024)
Land animals can be used to make a macroarthropodarium equipped with leaflets as well as a principle for embodying local wisdom in making learning media. The existence of a macroarthropodarium equipped with leaflets is very necessary and plays an important role in supporting the teaching and learning process of biology which is still considered abstract by students. This research aims to determine the feasibility of a macroarthropodarium equipped with leaflets as a biology learning medium in animalia material for class X even semester. This research uses a descriptive method with a qualitative approach through the distribution of learning media validation instruments on aspects of appearance, technical quality, size and terms that are validated by media experts. Judging from the appearance aspect, the macroarthroppodarium media equipped with leaflets got a score of 4.3, the scale aspect got a score of 4.5, the technical quality aspect got a score of 4.5, the size aspect got a score of 4.25, the language aspect got a score of 4.5 and the term aspect got a score of 4.25. Based on the validation results, the learning media in the form of a macroarthropodarium equipped with leaflets received a valid or suitable category for use at the next stage.